THE ROLE OF RS12901499 POLYMORPHISM IN ASSOCIATION WITH SMAD3 GENE AND OSTEOARTHRITIS SUSCEPTIBILITY: SYSTEMATIC REVIEW AND META-ANALYSIS - Li, Wenfei; Han, Fang; Song, Dandan; Shakir, Tahir Mehmood (Journal of Ayub Medical College Abbottabad, 2021)
Background: Osteoarthritis is regarded as one of the most frequent disorders of musculoskeletal, which is characterized by the degeneration of articular cartilage and loss of cartilage of the joints. However, the relationship of OA susceptibility with rs12901499 polymorphism in SMAD3 is controversial. Although multiple studies have investigated the correlation of rs12901499A/G polymorphism in SMAD family member 3 (SMAD3) and osteoarthritis (OA) susceptibility, the results from previous studies remain controversial and unsolved. A meta-analysis utilizing fixed and random effects model was performed to clarify the association. Methods:Eligible studies were systematically searched from PubMed, Web of Science, Cochrane Library and EMBASE on April 17, 2019 for reporting the correlation of rs12901499 polymorphism and osteoarthritis susceptibility. Pooled Odds ratio of 95% confidence interval was performed to estimate the strength of relationship of rs12901499 polymorphism and osteoarthritis susceptibility. Publication bias was detected by Begg’s test and STATA 11.0 software was used to evaluate statistical analysis. Results: Seven casecontrol papers involving eight studies from Caucasian and Asian populations were included. A significant increase in osteoarthritis susceptibility was found in recessive, homozygous and allele models. Stratified analysis on ethnicity suggested that the polymorphism with increased risk of OA only in Asians under allele model. Stratified analysis related to population-based studies indicated the increased risk of OA with polymorphism in recessive, homozygous, allele and dominant models. Conclusion:This meta-analysis demonstrated that there may be a weak association of rs12901499 polymorphism and OA susceptibility. Due to the limited size of sample and given ethnic groups, more studies need to validate the result in future.